2015
DOI: 10.1371/journal.pone.0131557
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphonuclear Cell Functional Impairment in Relapsing Remitting Multiple Sclerosis Patients: Preliminary Data

Abstract: Multiple Sclerosis patients run an increased risk of microbial infections, which leads to high rates of hospitalization and infection-related mortality. Although immunotherapy may increase infection risk in some cases, data as to the relationship among microbial factors, immunotherapy and alterations in the innate immunity of these patients are still scanty. On these grounds, this interdisciplinary study aims at investigating the role the functional activity of polymorphonuclear cells (PMNs) play in relapsing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…However, in this study, neutrophils from the treated group with normal oxidative burst demonstrated significantly reduced ability to kill bacteria (in vitro) [58]. Furthermore, in people with MS, with or without treatment, a slight reduction in neutrophil production of pro-inflammatory cytokines (IL-1β and IL-8) was found in response to bacterial stimulation (in vitro) [58].…”
Section: Role Of Neutrophils In Msmentioning
confidence: 83%
See 3 more Smart Citations
“…However, in this study, neutrophils from the treated group with normal oxidative burst demonstrated significantly reduced ability to kill bacteria (in vitro) [58]. Furthermore, in people with MS, with or without treatment, a slight reduction in neutrophil production of pro-inflammatory cytokines (IL-1β and IL-8) was found in response to bacterial stimulation (in vitro) [58].…”
Section: Role Of Neutrophils In Msmentioning
confidence: 83%
“…Secondary studies evaluating neutrophil phenotype and function in MS are prevalent and heterogeneous, producing no consensus as to the effects of disease on neutrophils or vice versa. Neutrophil oxidative burst studies either describe neutrophils as primed, exhibiting enhanced ROS production [24], or as normal, with similar ROS production, in healthy controls and people with MS, irrespective of treatment [58]. However, in this study, neutrophils from the treated group with normal oxidative burst demonstrated significantly reduced ability to kill bacteria (in vitro) [58].…”
Section: Role Of Neutrophils In Msmentioning
confidence: 87%
See 2 more Smart Citations
“…Polymorphonuclear leukocytes (PMNs) play a key role in the elimination of pathogens from the body through a wide range of effector functions [15][16][17][18][19][20]. As we have previously shown that PMNs isolated from RRMS patients display reduced intracellular killing activity [20], here we sought to determine whether treatment with first-line (moderate-efficacy) DMTs, such as IFNβ-1b (Extavia ® ) and GA (Copaxone ® ), or second-line (high-efficacy) DMTs, such as FTY (Gilenya ® ) and NAT (Tysabri ® ), would affect neutrophil functions in vitro.…”
Section: Introductionmentioning
confidence: 99%